Development of a triplex TaqMan probe-based real-time PCR assay for simultaneous detection of swine influenza virus, porcine reproductive and respiratory syndrome virus, and porcine circovirus type 2 - MengJie Wang; Yu Pan; Wengjie Ma; Xingrong Wang; Changyou Xia; Yue Wang (BMC Veterinary Research)
Abstract Background Porcine respiratory disease complex poses a substantial economic challenge for the swine farms due to its prevalence in pig farming environments. The disease is primarily caused by viral pathogens such as swine influenza virus (SIV), porcine reproductive and respiratory syndrome virus (PRRSV), and porcine circovirus type 2 (PCV2). Given the high incidence and morbidity associated with these viruses, effective control strategies rely on rapid and accurate diagnosis. Results To this end, we developed and validated a triplex TaqMan probe-based real-time PCR assay for the simultaneous detection and differentiation of SIV, PRRSV, and PCV2. This assay demonstrated high specificity, with no observed cross-reactivity between the target viruses. The assay’s sensitivity was determined to be 100 copies/µL for SIV and 10 copies/µL for PRRSV and PCV2. Comparison with a national standard detection method using 110 clinical samples revealed 100% agreement, confirming the reliability of the newly developed assay for clinical diagnostic applications. Conclusions Given the zoonotic potential of SIV, this assay not only provides a valuable diagnostic tool for veterinary medicine but also contributes to enhanced public health surveillance efforts.